TANGGUNG JAWAB PENGGUNA ANGGARAN/KUASA PENGGUNA ANGGARAN ATAS KERUGIAN KEUANGAN NEGARA - Darmansyah, Darmansyah (Katalogis, 2015)
The reseach was to identify the steps taken by a Budget User/Proxy of Budget User, causing state financial loss and subject to legal prosecutions under the prevailing corruption law and to recognize the accountabilities of the BudgetÂ User/Proxy of Budget User in case of state financial loss. It was a juriducal and normative reasearch adopting law and conceptual approaches. The legal materials were collected trough library research and prescriptively analyzed as well as deductively concluded. With reference to the the results of the research, it was concluded that the steps taken by a Budget User/Proxy of Budget User is concluded to have caused the financial loss when there was a manupilation of authorities to manage the state finance by both in order to illegally earn profits personally and/or for other parties or entities. In the perspectives of civil law, administration law and criminal law, it is provided that a Budget User is also accountable for the steps taken by a Proxy of Budget User in case the later causes state financial loss.